2024
DOI: 10.1029/2023je007841
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Stability of Salty Soil Seals in Mars‐Like Conditions. Implications for Methane Variability on Mars

Alexander A. Pavlov,
James Johnson,
Raul Garcia‐Sanchez
et al.

Abstract: Methane spikes observed in the Martian atmosphere require the abrupt release of large amounts of methane from the Martian subsurface. The mechanism for such release has not been identified. We tested whether gas traps can form under Mars‐like conditions in the shallow Martian regolith due to salt migration in the icy soil. Experiments were performed on various soil samples in a Mars Simulation Chamber comprising different perchlorate salts and water concentrations mixed with JSC Mars‐1A. Inside the chamber, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…14 Observation by the Curiosity rover found temporary spikes of methane and its rapid loss, but the mechanism of the loss has not been elucidated yet. Although some previous studies suggested a very local, small methane source near the landing site of the Curiosity rover, 15,16 an alternative possibility is the effective loss of methane via chemical reaction that is not considered in photochemical models. Mars’ soil is rich in iron oxides, where storms of iron-oxide particles (dust devils) occur very frequently.…”
Section: Introductionmentioning
confidence: 99%
“…14 Observation by the Curiosity rover found temporary spikes of methane and its rapid loss, but the mechanism of the loss has not been elucidated yet. Although some previous studies suggested a very local, small methane source near the landing site of the Curiosity rover, 15,16 an alternative possibility is the effective loss of methane via chemical reaction that is not considered in photochemical models. Mars’ soil is rich in iron oxides, where storms of iron-oxide particles (dust devils) occur very frequently.…”
Section: Introductionmentioning
confidence: 99%